2020
DOI: 10.1155/2020/9010937
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Amino Acid and Acylcarnitine Plasma Profiles for Distinguishing Patients with Multiple Sclerosis from Healthy Controls

Abstract: McDonald criteria and magnetic resonance imaging (MRI) are used for the diagnosis of multiple sclerosis (MS); nevertheless, it takes a considerable amount of time to make a clinical decision. Amino acid and fatty acid metabolic pathways are disturbed in MS, and this information could be useful for diagnosis. The aim of our study was to find changes in amino acid and acylcarnitine plasma profiles for distinguishing patients with multiple sclerosis from healthy controls. We have applied a targeted metabolomics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…It was already found in some studies that the levels of asparagine, glutamate, and N-acetyl-aspartate (NAA) were higher in plasma samples from patients with MS due to activation of the Asp biosynthesis pathway. This phenomenon was confirmed by Kasakin et al, 20 however their results of an increase in Asp concentration in their MS group and an increase in the glutamate concentration were not statistically significant. It should be emphasized that Asp, Glu, and other amino acids are related to the amino acid superpathway, and that their metabolism is connected to the tricarboxylic acid cycle and oxaloacetate and α-ketoglutarate intermediates; furthermore, Asp is a precursor of NAA.…”
Section: Discussionsupporting
confidence: 56%
“…It was already found in some studies that the levels of asparagine, glutamate, and N-acetyl-aspartate (NAA) were higher in plasma samples from patients with MS due to activation of the Asp biosynthesis pathway. This phenomenon was confirmed by Kasakin et al, 20 however their results of an increase in Asp concentration in their MS group and an increase in the glutamate concentration were not statistically significant. It should be emphasized that Asp, Glu, and other amino acids are related to the amino acid superpathway, and that their metabolism is connected to the tricarboxylic acid cycle and oxaloacetate and α-ketoglutarate intermediates; furthermore, Asp is a precursor of NAA.…”
Section: Discussionsupporting
confidence: 56%
“…Acylcarnitines also play an important role in energy metabolism by participating in the transfer of fatty acids into mitochondrial membrane [ 42 , 66 ]. Acylcarnitines, esters of L-carnitines and fatty acids, are important intermediates in metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Serum-based studies in MS have demonstrated that metabolomic signatures can be associated with more severe disease courses 5 and that kynurenine-pathway related metabolites can be used to differentiate between clinical phenotypes of MS, 6 validated in independent cohorts. Recent studies have focused on blood to diagnose MS, 7 , 8 , 9 , 10 to distinguish between RRMS and PMS, 11 , 12 and several have studied MS in the metabolome of cerebrospinal fluid (CSF), 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 which has been reviewed by Bhargava and Anthony. 21 …”
Section: Introductionmentioning
confidence: 99%